Sirolimus-induced regression of a large orbital lymphangioma. (2nd January 2019) - Lagrèze, Wolf A.; Joachimsen, Lutz; Gross, Nikolai; Taschner, Christian; Rössler, Jochen
ABSTRACT: Microcystic lymphatic malformations are difficult to treat surgically, especially when located in the orbital apex. Recently, pharmacologic inhibition of the mTOR pathway by sirolimus was reported as a safe and efficacious treatment option for lymphatic malformations (also known as lymphangiomas). We report the case of a young male patient in which a unilateral, retrobulbar lymphatic malformation regressed to a large extent under treatment with 1 mg sirolimus given orally twice a day over a period of six months.